(untitled) (KYAMC Journal, 2024)
Background: A common Presentation of thyroid disorder is solitary nodule. A discrete swelling in an impalpable gland is termed as solitary nodule of thyroid. The majority of solitary thyroid nodule are benign. The incidence of malignancy is more common in female with mean age 35 years. Timely intervention in nodular lesion of thyroid can significantly reduce morbidity and mortality. Objectives: The objective of this study was to evaluate the clinicopathological aspects of solitary thyroid nodule. Materials and Methods: This study was conducted in the department of otolaryngology and general surgery of Shaheed Monsur Ali Medical College and Hospital in 50 patients with Solitary Thyroid Nodule from July 2016 to July 2019. All the patients those who were diagnosed solitary thyroid nodule underwent thyroid surgery after through clinical evaluation, USG and FNAC. The histopathological reports were evaluated and correlated with clinical diagnosis and discussed. Results: Out of 50 patients’ majority were female only 8 were male patients. Peak incidence observed in the age group 30 to 40 years. Most of the patients presented with a swelling in front of neck 100% followed by pain 8%, dysphagia 4% and change of voice 4%. Swelling is located in the right lobe 70% followed by left lobe 26%. On FNAC examination they were presented with colloid nodular goitre 66%, follicular neoplasm 14%, thyroiditis 8%, papillary carcinoma 4% & cystic lesions 8%. But final histopathological report showed highest 30 (60%) cases was nodular goiter then follicular adenoma 10 (20%) and 6 (12%) were malignant. Conclusion: From this study we considered that STN is present most commonly in female. Most of them are benign, but remarkable proportion 12% of solitary thyroid nodule were malignant, so careful assessment of thyroid nodule is important for early diagnosis and treatment. KYAMC Journal Volume: 14, No: 03, October 2023: 161-164.